1995
DOI: 10.1007/bf01408102
|View full text |Cite
|
Sign up to set email alerts
|

Student counselling in Turkish universities

Abstract: Abstract. This article presents general information about the history, relevant laws and legislation, present status and anticipated future development in Turkish Universities, as well as the student counselling services within these institutions, Special emphasis is placed upon the perceived understanding of counselling as commonly accepted by the society, students and counsellors. While discussing the present status of Turkish University Counselling Centers, the proposed models, research findings and problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 1 publication
2
18
1
Order By: Relevance
“…This finding was consistent with the behavioral model of health-care utilization, which proposes that enabling resources such as availability, accessibility, and cost of services influences people's utilization of health services (Andersen, 1995). Similarly, lack of information about counseling services plays an important role in the underutilization of these services (Demir & Aydin, 1996;Erkin, 1994). Moreover, students might be inclined to misinterpret the role of these services because of inadequate knowledge.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding was consistent with the behavioral model of health-care utilization, which proposes that enabling resources such as availability, accessibility, and cost of services influences people's utilization of health services (Andersen, 1995). Similarly, lack of information about counseling services plays an important role in the underutilization of these services (Demir & Aydin, 1996;Erkin, 1994). Moreover, students might be inclined to misinterpret the role of these services because of inadequate knowledge.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, students might be inclined to misinterpret the role of these services because of inadequate knowledge. Demir and Aydin (1996) discussed that most students are not willing to obtain psychological assistance from counseling centres for fear of being stigmatized or labeled. Taken together, it was apparent that having accurate and adequate knowledge about psychological services generated a more positive perception toward help-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…1750), which went into effect in 1973. This law mandated that guidance and counselling services were to be carried out by academic advisors (Demir and Aydın 1997). Then, in 1984, through the Higher Education Law (Resmi Gazete No.…”
Section: History Of Counselling Centers In Turkish Universitiesmentioning
confidence: 99%
“…Thus, counseling as a field has been confronted with many of the same struggles as other social sciences in developing countries. In line with Adair and Kaǧıtçıbas ‚ı, Demir and Aydın (1996) concluded that although Turkish universities have been responsive in terms of keeping up with advances in academic fields, they have not been very responsive to the needs of society and, as a result, have turned out well-educated elites who perceive their social status to be above that of the general public. In short, many fields within the social sciences, including counseling, have had difficulties in perceiving the different social realities that exist in a country with a wide and continually changing spectrum of beliefs between the traditional and the modern.…”
mentioning
confidence: 93%